Follistatin-Like 3 Correlates With Lymph Node Metastasis and Serves as a Biomarker of Extracellular Matrix Remodeling in Colorectal Cancer - Yang, Chao; Cao, Fengyu; Huang, Shuoyang; Zheng, Yongbin (Frontiers in Immunology, 2021)
Background: As a heterogeneous disease, colorectal cancer (CRC) presents a great challenge to individualized treatment due to its lymph node metastasis (LNM). Existed studies have shown that immune and stromal components in extracellular matrix (ECM) act as important part in tumorgenicity and progression, while their roles in LNM has not been fully elucidated. Here, crucial ECM-related genes responsible for LNM in CRC were selected by multi-omics analysis. Methods: Firstly, we characterized the immune infiltration landscape of CRC samples from the TCGA and GEO databases using ssGSEA algorithm. The CRC patients were divided into several immune subgroups by hierarchical clustering analyses. Then, differential genes were identified among immune subgroups and CRC vs. normal tissues in TCGA and GEO cohorts, respectively. Next, weighted correlation network analysis (WGCNA) was employed to construct a co-expression network to find LNM-related modules and hub genes. Subsequently, we evaluated the clinically valuable of hub gene in prognostic prediction and chemotherapy/immunotherapy. Besides, the protein level of key gene was verified in a external cohort from our center. Finally, we explored the underlying mechanism of FSTL3 -mediated LNM by Gene function annotation and correlation analysis. Results: Two immune subgroups, namely Immunity_High and Immunity_Low, were defined among the two CRC cohorts using ssGSEA algorithm, respectively. Based on the two immune subgroups, 2635 overlapping differentially expressed were obtained from two cohorts, which were sequentially subjected to WGCNA and univariate Cox regression analysis. Ultimately, FSTL3 was selected as the key gene. Here, we first confirmed that overexpression of FSTL3 correlated with LNM and worse prognosis in CRC, and were verified at the protein level in the external validation cohort. Moreover, FSTL3 expression showed strongly positive correlation with immune and stromal components in ECM. We furthermore found that FSTL3 may accelerate LNM through the formation of inhibitory immune microenvironment via promoting macrophage and fibroblasts polarization and T cell exhaustion. Interestingly, high FSTL3 expression is linked to the chemoresistance, but to immunotherapy-sensitive. Conclusion: FSTL3 is identified as a biomarker for ECM remodeling and worse clinical outcomes for the first time in CRC, and is also a potential immunotherapeutic target to block LNM for CRC.